THE IMPACT OF AGE ON OUTCOMES OF CORONARY ARTERY BYPASS GRAFTING - SALEEM, M; SAEED , MA; IQBAL, H (Biological and Clinical Sciences Research Journal, 2023)
As people live longer, the number of individuals aged 75 and above is increasing. This makes it crucial to provide careful medical care for elderly cardiac patients. Our study was conducted at the Punjab Institute of Cardiology and involved 300 patients divided into three age groups: those under 60, those between 60-75, and those over 75. Participants had no history of cardiac surgery. We documented preoperative demographics and other relevant variables and then analyzed post-operative data concerning complications and other variables separately for each age group. Our research revealed a significant association between age and 30-day mortality (p < 0.001), with a 2.5% incidence of 30-day mortality observed among those over 75 years old. We also found that re-intubation, dialysis, extended ICU stays, and atrial fibrillation occurred more frequently in the over-75 age group compared to other age groups (P < 0.001). Our findings highlight the significant impact of age on mortality after cardiac surgery, as well as the heightened likelihood of complications in elderly individuals. Therefore, it is essential to carefully consider age-related organ abnormalities and the increasing burden of age-related health problems when managing elderly patients who undergo cardiac surgery. These insights suggest a need for personalized strategies to address the unique challenges posed by advanced age in the context of cardiac surgical procedures.